ANALISIS KESULITAN BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII DALAM MEMAHAMI KONSEP BILANGAN BERPANGKAT - Okti Indah Elvita; Sri Yunita Ningsih (Ensiklopedia Research and Community Service Review, 2026)
This study aims to describe and analyze the learning difficulties of eighth-grade students in understanding the concept of exponents. The research employed a qualititative method with a descriptive approach and  was conducted at MTs Nurul  Falah Airmolek. The subjects consisted of eighth-grade students from five classes and a mathematics teacher as a supporting informant. Data were collected through essay test and interviews. The results showed that students experienced difficulties in understanding the basic concept of exponents, applying the properties of exponents, and solving word probems. These difficulties were caused by weak conceptual understanding and low mastery of basic multiplication operations. In addition, students  demonstrated misconceptions regarding exponent rules, such as zero exponents and operations involving multiplication and vision of exponents. The findings indicate that students” understanding of material is not evenly distributed across classes. Therefore, more concrete, gradual, and continuous practice-based learning is needed to improve students’ conceptual understanding.Keywords:  Learning Difficulties, Mathematics, Students, Conceptual Understanding, Exponents